Effects of Fruit Maturity Stages on GC-FID Fatty Acid Profiles, Phenolic Contents, and Biological Activities of Eucalyptus marginata L. - Hanene Ghazghazi; Badiaa Essghaier; Ichrak Jawadi; Leila Riahi; Ridha Ben Salem; Ghayth Rigane (Journal of Food Quality)
The objective of this study was to determine the impact of development stages of Eucalyptus marginata’s fruits on the fatty acid composition as well as on phenolic, flavonoid, and tannin contents of oils. Taking into account fruit maturity stages, vegetable oils have been evaluated for their biological potentials. Fatty acid profiles were quantified using gas chromatography (GC) coupled to a flame ionization detector (FID). The fatty acid profiles of oils obtained from mature fruits showed highest linoleic acid content (49.21%) and Z-vaccenic (C18:1n-7) + oleic (C18:1n-9) acids (22.40%) and a low content of linolenic acid (C18:3) (1.59%). On the other hand, the major saturated fatty acid compound found in the oil of immature Eucalyptus marginata fruits was palmitic acid (C16:0) with about 27%. Based on the Folin–Ciocalteau method, the obtained results revealed a significant difference in the contents of total polyphenols, flavonoids, and tannins according to the stage of fruit maturity (p<0.05). Furthermore, the detected antimicrobial potentials were related to the fruit maturity stage. While both veg\etable oils extracted from mature and immature Eucalyptus marginata fruits exhibited notable antibacterial activities against the species Staphylococcus aureus, Enterococcus faecalis, Serratia marcescens, and Escherichia coli, only the oils extracted from immature fruits exhibited an antifungal activity against Candida parapsilosis.